Analisis Penerapan Akuntansi Lingkungan (Environment Accounting) Pada Pt Pemuka Sakti Manis Indah Di Way Kanan Lampung - Ulkaromah, Anisa; Suyanto, Suyanto; Nusantoro, Jawoto (Universitas Muhammadiyah Metro, 2023)
The purpose of this study is to find out whether the company has implemented environmental accounting and conformity with PSAK 2022. This research method uses qualitative research to analyze the application of environmental accounting at PT Pemuka Sakti Manis Indah in Way Kanan Lampung, which is located in the village Mount Waras, Way Kanan District, Lampung Province. The results of the study show that PT Pemuka Sakti Manis Indah is in accordance with PSAK 2022 concerning recognition, measurement and presentation that correctly recognizes the cost of waste treatment and measurement of the cost of treating the waste as referred to in PSAK 2022 paragraph 1 concerning financial reports. The presentation of PT Pemuka Sakti Manis Indah's waste treatment costs is appropriate, by presenting clearly the financial position. PT Pemuka Sakti Manis Indah presents the cost of treating waste presented in processing in production costs, in the Company's Profit and Loss Report in Cost of Goods Sold.